Cloning and Characterization of 5-enopy ruvylshikimate-3-phosphate Synthase from Fragaria vesca - Liu,Feng (2021)
Abstract To discover and isolate a glyphosate-resistant gene from Fragaria vesca through gene mining. An open reading frame (ORF) of 1563 bp encoding EPSPSwas amplified from Fragaria vesca (FvEPSPS). FvEPSPS (Genebank: XP004306932.1) encodes a polypeptide of 520 amino acids and it has hightly homologous with EPSPS from other plants. qRT-PCR analysis showed that the FvEPSPS was expressed extensively in all tissues including leaves, roots and stems, with higher expression in leaves. Furthermore, transgenic Arabidopsis Thaliana exhibited 10 mM glyphosate to resistance. Therefore, this research offers a new glyphosate-resistant gene for development of transgenic crops.